Dinamika Sharing Teman Sebaya dalam Menghadapi Stress Akademik pada Santri Mahasiswi dengan Tuntunan Peran Ganda - Karima, Qonita Karima; Saiful Islam; Choirul Mahmudi (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study aims to explore forms of academic stress experienced by female student-santri and to analyze the dynamics of peer sharing as a coping strategy in an Islamic boarding school context that requires dual roles as university students and santri. This study is based on the limited research explaining the gradual emergence of coping processes, particularly the timing and emotional support function of peer relationships. Design/methods – This study employs a qualitative approach with a phenomenological design to understand participants’ subjective experiences. Informants were selected purposively, consisting of female student-santri as the main informants, supported by pesantren administrators and close peers. Data were collected through in-depth interviews, participatory observation, and documentation. The data were analyzed thematically using an interactive analysis model through data reduction, categorization, verification, and conclusion drawing. Findings – The findings show that academic stress emerges when academic and pesantren demands are perceived as exceeding individuals’ internal resources. In line with Lazarus and Folkman’s transactional theory of stress, stress occurs through primary appraisal and secondary appraisal before coping strategies are determined. Peer sharing does not appear as an initial response but emerges after independent coping efforts are perceived as less effective. This study identifies two conceptual contributions: relational coping bridge, which functions as an emotional bridge for restoring psychological balance, and delayed social coping activation, which explains the activation of social coping after internal coping becomes inadequate.